Writing while wandering: Material and spatial contingency in locative media narratives. (February 2017) - Fan, Lai-Tze
In digital writing, there is a discrepancy between the dynamicism that is associated with born-digital narratives and the rigidly encoded structures of content management that shape digital media technologies. Locative media narratives – site-specific narratives that are designed for accessing digital mobile devices – are therefore interesting because they cannot be written without reference to real space and are subject to the dynamic relationships that device users have with material space. This article reveals the ontological complexities of digital reading and digital writing for the locative media narrative user. Writing and reading digitally through locative media narratives, I argue, require users' dynamic and reflexive negotiation between the experience of reading and the material circumstances that offer insight into the element of contingency in digital writing. Specifically, I explore the element of contingency as a 'counter' to paradigms of standardization and rationalization during the age of modernity; its nullification through the introduction of predefined digital parameters; its resilience in the figure of the walker; and its contemporary resilience in the media user. Contingency is thus delineated as a condition through which a dynamic narrative can emerge between the parameters of digital writing and a user's narrative play. The material spaces explored are contingent upon which paths users choose to take; also, the produced story is contingent upon the narrative trajectory that is formed through users' wandering through material space. As users choose real spaces with historiocultural contexts, this article shows that locative media narratives allow us to write digital narratives while also engaging in the discourses of material space, media materiality, and emerging forms of narrative. In turn, by conceptualizing and identifying dynamic forms of narrative for how they complicate notions of reading and writing, this article proposes the initial shaping of a narratology for dynamic digital narratives.